The oxidation-resistant Mo30Si60B10 coating for protection of the T2 phase-based molybdenum alloy - A.D. Chertova; A. Yu. Potanin; P. Feng; X. Ren; E.A. Levashov; Ph. V. Kiryukhantsev-Korneev (Open Ceramics)
This study focuses on fabrication of a Mo30Si60B10 coating with elevated silicon content, which enhances working properties of Mo-alloy based on the Т2 phase (t-Mo5SiB2). The Mo30Si60B10 coating has a columnar structure. The alloy is characterized by hardness of 17 GPa; Young's modulus of 304 GPa, and elastic recovery of 29 %. Deposition of the coating increased hardness by 40 %; the Young's modulus, by 18 %; and elastic recovery, by 25 %. Oxidation tests at 1200 °C demonstrated that the specific mass loss of the alloy with Mo30Si60B10 coating was 1.5-fold lower than that of the uncoated alloy. An 18 μm thick oxide layer based on a-SiВO and containing MoO2 particles was formed on the alloy surface. The coating contributes to a ∼14-fold reduction of oxide layer thick. The increase in oxidation resistance of alloy after coating deposition is related to sealing of substrate defects and formation of an a-SiВO layer with elevated silicon content.